Hubungan Pola Asuh Orangtua dengan Hubungan Sosial Siswa - Nofrizal Nofrizal (Journal of Pedagogy and Online Learning, 2023)
This study aims to describe the parenting style, social relationships of students in SMP Negeri 13 Padang.This study uses a descriptive approach and simple linear correlation analysis. The sample of this study was 273 students. Sampling using simple random sampling technique. The instruments used were the "parenting scale" with a reliability value of 0.721, and the "social relationship scale" with a reliability value of 0.726. The results showed that: (1) the parental pattern was included in the good category with a percentage of 85%. (2) Student social relations are included in the very good category with a percentage of 56.16%. (3) the correlation of parenting style with students' social relationships with a correlation coefficient of 0.452. The results of this research can be used as material for BK teachers in providing guidance and counseling services in schools by establishing good communication and cooperation between the school, parents and students to strive to improve student social relations.